2019
DOI: 10.1111/jfbc.12898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal and microwave processing on secondary structure of bovine β‐lactoglobulin: A molecular modeling study

Abstract: Milk allergy is known to cause severe allergic reactions in hypersensitive patients, especially in infants and children. β‐Lactoglobulin is one of the major allergens in bovine milk. The influence of thermal and microwave processing on the structural deviations of β‐lactoglobulin protein have been studied using molecular modeling techniques. The structural deviations are studied using root mean square deviations, radius of gyration, dipole moment, and solvent accessible surface area. STRIDE analysis showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
(82 reference statements)
0
13
0
1
Order By: Relevance
“…. ] and solvent accessible surface area" and analyzed using the STRIDE algorithm [16,34]. The calculation of the root mean square deviation (RMSD) assigns a quantitative value to the structural deviations that occur through the simulation, as it compares the final coordinates of the atoms in the studied molecule to the atoms' initial coordinates before the imposition of external stress [17].…”
Section: Gromacs Software Package For Molecular Dynamics Simulationmentioning
confidence: 99%
See 4 more Smart Citations
“…. ] and solvent accessible surface area" and analyzed using the STRIDE algorithm [16,34]. The calculation of the root mean square deviation (RMSD) assigns a quantitative value to the structural deviations that occur through the simulation, as it compares the final coordinates of the atoms in the studied molecule to the atoms' initial coordinates before the imposition of external stress [17].…”
Section: Gromacs Software Package For Molecular Dynamics Simulationmentioning
confidence: 99%
“…Elsewhere, Saxena et al [16] applied thermal and oscillating electric fields to the common allergen β-lactoglobulin protein present in cow's milk. In this study, the AMBER99SB-ILDN force field was utilized, and, considering the net negative charge (−14e) of the βlactoglobulin protein, it was neutralized with fourteen positively charged sodium ions [16]. This particular modeling study identified the important effect the treatments had on epitopes that lead to IgE-mediated allergic reactions by the immune system.…”
Section: Ns [18]mentioning
confidence: 99%
See 3 more Smart Citations